Using maternal rescue of pups in a cup to investigate mother-infant interactions in mice/rodents - Esposito, Gianluca (2019)
Efficient parental care is indispensable for survival of the mammalian offspring, and therefore both parents and offspring cooperate to achieve the best performance. For example, when parents transport altricial offspring, the offspring immediately respond by reducing its cry and movement in both human infants and rodent pups. This coordinated set of central, motor and cardiac responses is designated as the Transport Response (TR) and is shown to facilitate maternal carrying in rodents. The present study aims to investigate the core behavioural characteristics of mother-infant interaction, and to investigate the mechanisms underlying the mother-pup cooperation using pharmacological and genetic manipulations (i.e. Oprm1-/). Along with the clear developmental changes of the pups' immobility and posture during maternal carrying as previously reported, there were also adaptations in maternal strategies, particularly in positioning of foothold and oral grasp over the pup's body, with the pups' age and pup's behaviour. Tree-based models elucidated that both of these maternal variables as well as percentage of pups' struggle predict the time required for pup retrieval from a cup. When the sensory-motor control in pups was disturbed by pharmacological or genetic manipulations, these core behaviours were inefficiently performed and impede maternal retrieval. Mother-infant mutual fit is a complex construct where several intermingled mechanisms are involved. Thus mothers and infants, when interacting, should be considered together as one whole system in which any change in one side or the other, affects the output of the whole dyad. The outcome of the interaction relays on a specific dynamic pattern of infant and maternal behaviours, which mutually change and adapt to fit each other's needs. Key features to reach a successful outcome of the interaction were the maternal retrieving strategy and infants’ Transport Response behaviour.